Targeting property flood resilience in flood risk management. Issue 3 (7th May 2021) - Webber, James L.; Chen, Albert S.; Stevens, John; Henderson, Rob; Djordjević, Slobodan; Evans, Barry
Abstract: In this article, we evaluate property flood resilience (PFR) to manage pluvial and combined tidal/ fluvial flood risks. We achieve this by evaluating flood risk and intervention targeting strategies across a case study in Bristol (UK) using data types generally available for preliminary option assessment. We investigate opportunities for mitigating flood damages within catchments using PFR and evaluate two targeting strategies: Installing PFR across strategic areas of a catchment and targeting interventions at specific high‐risk properties. We find that individually targeting PFR is more effective than focusing resources on specific high‐risk areas. Targeting pluvial flood measures at individual properties across our case study provides an average annual benefit per property of approximately £750 more than applying zonal targeting, supporting use of high‐resolution modelling in surface water management, and highlighting the applicability of PFR to manage damages at specific high‐risk properties which may not fall under the protection of community level defences. A similar approach provides the best outcomes for fluvial targeting; however, the hazard is more concentrated and so a zonal targeting approach may be more acceptable. Overall, we find resistance based PFR an effective intervention to mitigate damages, however complementary strategies are required when managing extreme flooding.